Voice Command Wheelchair Control Using Bluetooth For Disabled Patients - Hindarto, Hindarto; Arief Wisaksono; Ade Efiyanti; Egha Arya (Computing and Information System Journal, 2025)
Disability is a physical or mental condition that limits a person's ability to fully participate in daily activities. Disabilities can occur to anyone and may be temporary or permanent. Examples of physical disabilities include vision loss, deafness, or mobility limitations, while examples of mental disabilities include autism spectrum disorders, anxiety disorders, or depression. People with disabilities often require environmental adjustments and community support to participate fully in daily life. This study focuses on individuals with leg disabilities, and one of the tools used by those with such disabilities is the wheelchair. There have been numerous studies on wheelchairs for individuals with leg impairments. In this research, the wheelchair is controlled using voice commands, which include forward, backward, left, right, and stop commands. To implement the wheelchair control, an Arduino Uno is used to process voice commands from the user, which are converted into text on an Android device. The text is then sent via Bluetooth and received by the Arduino Uno through serial communication. The control from Android to Arduino Uno is conducted in real-time, allowing the wheelchair to move according to the commands given. The result of this research shows that wheelchair control using voice commands was 100% successful